(untitled) (Research, Society and Development, 2025)
Technology has greatly transformed the practice of dentistry, bringing innovations that improve diagnosis, treatment and patient management. The aim of this article is to analyze technological advances in modern dentistry and their ethical implications, using the fundamental principles of bioethics: autonomy, beneficence, nonmaleficence and justice. The aim is to provide a framework for responsible and equitable clinical practice, promoting an ethical integration of technologies in dentistry. The study is of a narrative type, based on the collection, analysis and critique of bibliographic data obtained from various academic platforms such as MEDLINE, Google Scholar, PubMed, Wiley, Lilacs and Scielo, in addition to journals, theses and books. The search also included the review of the bibliography referenced in the selected documents. The conclusion of the article highlights that the use of advanced technologies in dentistry represents an opportunity to transform dental care. However, it also requires an ethical commitment on the part of practitioners to ensure that these innovations benefit all patients. Integrating bioethical principles into daily practice is essential to ensure that new technologies respect patients’ rights, promoting more accessible and equitable dental care.